Initial experiences of switching to faricimab for neovascular age-related macular degeneration and polypoidal choroidal vasculopathy in an Asian population - Ibrahim, Farah N. I.; Teo, Kelvin Y. C.; Tan, Tien-En; Chan, Hiok Hong; Chandrasekaran, Priya R.; Lee, Shu-Yen; Tan, Anna C. S.; Mathur, Ranjana; Chan, Choi Mun; Sim, Shaun S.; Tan, Gavin Siew Wei; Yeo, Ian Y. S.; et al. (Frontiers in Ophthalmology, 2024)
To describe early experience in patients with neovascular age-related macular degeneration (nAMD) and polypoidal choroidal vasculopathy (PCV) whose treatment was switched to faricimab from other anti-VEGF agents.This is a prospective cohort of eyes with nAMD and PCV previously treated with anti-VEGF agents other than faricimab. We evaluated visual acuity (VA), central subfield thickness (CST), macular volume (MV), pigment epithelial detachment (PED) height and choroidal thickness (CT) after one administration of faricimab. Where present, fluid was further evaluated according to intraretinal fluid (IRF), subretinal fluid (SRF) or within PED.Seventy-one eyes from 71 patients were included (45.07% PCV and 54.93% typical nAMD). Mean (standard deviation (± SD) VA, CST and MV improved from 0.50 (± 0.27) to 0.46 (± 0.27)logMAR, p=0.20, 383.35(± 111.24) to 322.46(± 103.89) µm, p<0.01,and 9.40(± 1.52) to 8.75(± 1.17)mm 3 , p<0.01 from switch to post switch visit. CT reduced from 167(± 151) to 149(± 113)µm, p<0.01. There was also significant reduction in maximum PED height between visits, 302.66(± 217.97)µm and post switch visit 236.66(± 189.05)µm, p<0.01. This difference was greater in PEDs that were predominately serous in nature.In eyes with typical nAMD (n=39), improvements were significant for CST, MV, CT and PED. In eyes with PCV (n=32), only reductions in CT were statistically significant, while VA, CST, MV and PED only showed numerically smaller improvements. One patient developed mild vitritis without vasculitis, which resolved with topical steroids with no sequelae.In our series of Asian nAMD, switching to Faricimab was associated with stable visual acuity and meaningful anatomical improvements, particularly with typical nAMD subtypes.